2001
DOI: 10.1002/ccd.1124.abs
|View full text |Cite
|
Sign up to set email alerts
|

Late stent thrombosis in the absence of prior intracoronary brachytherapy

Abstract: Late stent thrombosis has not been reported in the absence of prior coronary brachytherapy. We reviewed our experience in 1,855 consecutive patients who received at least one stent and did not receive coronary brachytherapy. Half of all stent thromboses occurred within the first week and nearly 65% (22) occurred within 15 days. The incidence of stent thrombosis within this traditional time frame was 1.2%. An additional 12 patients, however, presented with stent thrombosis between 33 and 270 days post-procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 0 publications
1
22
1
Order By: Relevance
“…1,2) Although the in-stent thrombosis could not be directly confirmed with thrombectomy and was not directly observed by IVUS or angioscope, the angiographical radiolucency at the prior stent ( Figure 2B & C) strongly suggested that AMI was induced by stent thrombosis. Angiographic radiolucency in case of ACS is considered to be an athero-thrombus which is the genesis of ACS, and prior reports concerning LST 1,2) were also diagnosed as LST with an angiogram (radiolucency). Therefore, the lack of direct evidence of thrombotic intrastent occlusion is a limitation for the clinical diagnosis in these cases.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…1,2) Although the in-stent thrombosis could not be directly confirmed with thrombectomy and was not directly observed by IVUS or angioscope, the angiographical radiolucency at the prior stent ( Figure 2B & C) strongly suggested that AMI was induced by stent thrombosis. Angiographic radiolucency in case of ACS is considered to be an athero-thrombus which is the genesis of ACS, and prior reports concerning LST 1,2) were also diagnosed as LST with an angiogram (radiolucency). Therefore, the lack of direct evidence of thrombotic intrastent occlusion is a limitation for the clinical diagnosis in these cases.…”
Section: Discussionmentioning
confidence: 98%
“…1,2) According to a small retrospective study, 2) LST was reported to occur in a similar proportion of patients (a few percent) as acute and subacute thrombotic occlusion after stenting, suggesting that LST is not rare and should be emphasized as an important late complication after stenting. Although the known causative factors of early stent thrombosis 4,5) and ISR in its chronic phase (about six months after implant) 6) were not relevant to this case ( Figure 1D), abrupt thrombotic occlusion at the prior stent could be triggered and induced by abnormal endothelialization on the stent strut: ie, lack of endothelialization, 7) residual red thrombus, 7) rupture (or dissection) of hyperplasic neointima due to persistent arterial inflammation at the stenting site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have confirmed that stent thrombosis occurring at any time point following either bare metal stent (BMS) or DES implantation is a very serious adverse event associated with high rates of death and nonfatal myocardial infarction (3)(4)(5)(6)(7). During 2006, dissemination of the results of the Basel Stent Cost-effectiveness Trial -Late Thrombotic Events (BASKET-LATE) (8) and other DES trial metaanalyses (9,10) raised widespread concerns about an increase in late (more than 30 days) and very late (more than 12 months) stent thrombosis in patients treated with DES compared with those receiving BMS.…”
mentioning
confidence: 99%